Effect of photoinitiator concentration on marginal and internal adaptation of experimental composite blends photocured by modulated methods - Bruschi Alonso, Roberta Caroline; Carvalho de Souza-Júnior, Eduardo José; Dressano, Diogo; Spagnolo de Araújo, Giovana Albamonte; Ces Rodriguez, José Manuel; Hipólito, Vinícius Di; Anauate-Netto, Camillo; Puppin-Rontani, Regina Maria; Coelho Sinhoreti, Mario Alexandre (European Journal of Dentistry, 2013)
Objective: The aim of this study was to evaluate the influence of photoinitiator concentration on marginal and internal adaptation of composites photocured by modulated methods. Materials and Methods: Composites based on BisGMA/triethylene glycol dimethacrylate and 65 wt% of filler were prepared with different concentrations of camphorquinone/amine (C1-0.5%, C2-1%, C3-1.5%). Cavities were prepared (3 mm × 3 mm × 2 mm) on the buccal surface of 120 bovine incisors and the adhesive system Adper Single Bond 2 was applied following manufactures instruction. Specimens were then distributed according to type of composite (C1, C2, C3) and photoactivation method (high-intensity - 750 mW/cm 2 for 40 s; low intensity - 150 mW/cm 2 for 200 s; soft-start - 150 mW/cm 2 for 10 s + 750 mW/cm 2 for 38 s; pulse-delay - 150 mW/cm 2 for 10 s + 3 min dark + 750 mW/cm 2 for 38 s). Superficial and internal margins were analyzed by scanning electron microscopy, using the epoxy replica technique. The length of gaps was expressed as a percentage of the total length of the margins. Data were submitted to two-way analysis of variance and Tukey′s test (α =0.05). Results: Modulated curing methods did not influence gap formation regarding both superficial and internal adaptation. The composite with the lower initiator concentration (C1) presented higher gap formation when compared with those with higher concentrations (C2 and C3).Conclusion:Modulated photoactivation methods did not reduce gap formation for the experimental composite restorations evaluated. However, higher photoinitiator concentrations promote better marginal seal.
Keywords: Camphorquinone; gap formation; modulated photoactivation methods; pulse-delay; resin composites; soft-start